Evaluation of freeze-dried pregelatinized Chinese yam (Dioscorea oppositifolia) starch as a polymer in floating gastroretenive metformin microbeads. (2010)
Pregelatinized Chinese yam (Dioscorea oppositifolia) starch has been evaluated as a polymer for the formulation of floating gastroretentive beads for the controlled delivery of metformin hydrochloride. Floating microbeads were prepared by the ionotropic gelation method using a blend of modified Chinese yam starch and sodium alginate at different ratios. Sodium bicarbonate was added as a gas-generating agent. The floating microbeads were characterized by SEM, DSC, FTIR analyses and the drug entrapment efficiency and floating ability was evaluated. Drug release was investigated using in vitro dissolution test and the results were fitted to various kinetic models to determine the mechanism(s) of release. Spherical, discrete and free flowing microbeads were obtained from the modified starch-alginate blends. Minimum lag time (< 20 s) was observed for the floating microbeads containing starch and buoyancy was maintained for 12 h. The release of MET from the floating microbeads appeared to be controlled by varying the starch to alginate polymer ratio. In general, the formulations followed diffusion and erosion mechanisms of drug release. The results suggest that modified Chinese yam starch-sodium alginate blend can be useful for the formulation of floating gastroretentive system for metformin hydrochloride